INCREASE OF FOOD WASTE BASED ON FOOD TEMPERATURE AND FREQUENCY OF CHEMOTHERAPY BREAST CANCER PATIENT - Hapsari Sulistya Kusuma; Laila Hidayati; Salsa Bening (Jurnal Riset Kesehatan, 2020)
Food waste is one of the simple indicator that can be used to evaluate the success of the nutrition service of the hospital.One of the factors is frequency of chemotherapy can affect the occurrence of food waste, which aims to analyze the relationship of temperature and frequency of chemotherapy against food waste on breast cancer in patients was Dr. Kariadi Semarang. This type of research is observational research with cross sectional study approach. The research sample is 16 breast cancer patient who was elected in consecutive sampling. Statistical analysis using correlation Pearson Test to know the relationship of temperature and frequency of chemotherapy against food waste on breast cancer in patients was Dr. Kariadi Semarang. Of the total sample as much as 62.5% of the 16 people on the age group 45-64 years. The temperature of the food including the danger zone (45oC – 60oC). The food waste of staple 30.87 ± 13.58, animal side dish 42.43 ± 15,72, vegetable side dishes 35,81 ± 17,95 , vegetable 37.62 ± 18.39. The results of this research was there is a correlation between food waste and food temperature in vegetable (p = 0.038).There was a correlation between frequency of chemotherapy and food waste in staple food with (p=0.567). There was a correlation between frequency of chemotherapy and food waste in vegetable side dish with (p=0,006). There was a correlation between frequency of chemotherapy and food waste in animal side dish with (p=0,028). There was a correlation between frequency of chemotherapy and food waste in vegeteble (p=0,004). There was a correlation between the food temperature and food waste of vegetable menu. There was a relationship between frequency of chemotherapy with food waste of staple food, animal side dish, vegetable side dish and vegetable.